Strategy for Increasing Interest in Muzakki Through Digital Payment Applications: Case Study in Baznas Jombang - Sofiyah, Fitriyatus; Nasrulloh, Nasrulloh (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2023)
In this digital era, many institutions have implemented digital payments as a tool for transactions easily and efficiently. But there are still many people in general, especially Muzakki, who don't know how to make transactions via digital payments. This causes people's interest in becoming muzakki in giving zakat to not increase due to several factors such as a lack of understanding about what digital payments are used, then a lack of socialization regarding the benefits of digital payments for muzakki. institutions must socialize about Digital Payment so that it is easier for Muzakki to carry out zakat transactions. The research methods used by researchers are descriptive qualitative methods and case studies. By writing this journal, researchers can conclude that the existence of digital payments which have been implemented by the Jombang national zakat amil institution (BAZNAS) is not widely known by the community as a whole. So the public's interest in becoming muzakki has increased but not too significantly. Of the many digital payments used by institutions, many muzak choose to transact via banks.Keywords: Digital Payment, Interest, Muzakki, Zakat